2018
DOI: 10.1074/jbc.ra117.000245
|View full text |Cite
|
Sign up to set email alerts
|

Sal-like 4 protein levels in breast cancer cells are post-translationally down-regulated by tripartite motif–containing 21

Abstract: Keywords:On the list: breast cancer, E3 ubiquitin ligase, molecular biology, protein degradation, transcription factor Not on the list: Ro52, SALL family, SALL4, TRIM21 http://www.jbc.org/cgi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
(1 reference statement)
1
13
0
1
Order By: Relevance
“…S100A10, a small dimeric helix-loop-helix protein residing in a tight complex with Annexin A2, appeared to regulate the intracellular trafficking of a variety of membrane-resident proteins, such as cathepsin B (38). TRIM21 is an E3 ubiquitin ligase associated with autoimmune diseases (39), and the dysregulation of TRIM21 facilitates human cancer development (40,41). This study detected a significant decrease of TRIM21 and Annexin A2 levels in PGCCs with their daughter cells after S100A4 knockdown as well as a reduced nuclear translocation of S100A10 in daughter cells, while 14-3-3 ζ/δ and Ezrin did not vary.…”
Section: Discussionmentioning
confidence: 99%
“…S100A10, a small dimeric helix-loop-helix protein residing in a tight complex with Annexin A2, appeared to regulate the intracellular trafficking of a variety of membrane-resident proteins, such as cathepsin B (38). TRIM21 is an E3 ubiquitin ligase associated with autoimmune diseases (39), and the dysregulation of TRIM21 facilitates human cancer development (40,41). This study detected a significant decrease of TRIM21 and Annexin A2 levels in PGCCs with their daughter cells after S100A4 knockdown as well as a reduced nuclear translocation of S100A10 in daughter cells, while 14-3-3 ζ/δ and Ezrin did not vary.…”
Section: Discussionmentioning
confidence: 99%
“…First, TRIM21 was capable of ubiquitylating and degrading oncoproteins involved in the maintenance of cell stemness, such as SALL4 and OCT1. 10 , 12 Second, TRIM21 was able to affect the progression of the cell cycle, autophagy, and apoptosis via modulating expression of p53, SQSTM1/p62, and Par-4. 11 , 24 , 25 Third, TRIM21 is involved in the regulation of glycolysis and DNA repair by downregulating DDX41 and phosphofructokinase 1 platelet isoform.…”
Section: Discussionmentioning
confidence: 99%
“… 11 In breast cancer, TRIM21 was found to be capable of downregulating the expression of Sal-like 4 (SALL4) and Lifeguard. 12 , 13 However, the clinical significance of TRIM21 and its role in cell proliferation in breast cancer remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…TRIM21 is a multifunctional protein and its role as an intracellular antibody receptor in immune responses has been extensively studied. As an E3 ligase, TRIM21 targets several substrates involved in innate and adaptive immunity and cancer development, including sequestosome 1 (SQSTM1/p62) ( 39 ), mitochondrial antiviral signaling protein ( 40 ), and multiple members of the interferon regulation factor (IRF) protein family (IRF3/5/7/8) ( 41 , 42 , 43 , 44 ). Our study has identified ion channels as a target of TRIM21 E3 ligase for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, decreased TRIM21 protein and mRNA expression has also been linked to several cancers. For example, TRIM21 suppresses colorectal and breast cancers by ubiquitinating and causing the degradation of, respectively, serine hydroxymethyltransferase 2 ( 44 ) and the transcription factors Sal-like proteins 1 and 4 ( 42 ); moreover, TRIM21 downregulation in breast cancer is closely correlated with the large tumor size and poor prognosis ( 54 ). Conversely, elevated TRIM23 expression has been suggested to be associated with poor prognosis in gastric cancer ( 55 ) and HNSCC ( 56 ).…”
Section: Discussionmentioning
confidence: 99%